A eleição de “heróis” pioneiros na revolta dos posseiros de 1957 no sudoeste do paraná - Zatta, Ronaldo; Rippel, Leomar (Universidade Federal Rural do Rio de Janeiro, 2015)
The public representatives’ ideological and idealistic constructions, through cuttings merely ethnical, interlinked with the exaltation and celebration of the Revolt of the Leaseholders in the Southwest area of Paraná they were intensified in the last decade on the part of the constituted regional authorities, what is drawing attention from social scientists. In this sense we were also in spired to discuss the relationship of the construction of these characters together “firsts” such as consolidation, sedimentation, regional official of the memory, taking into consideration that the imagination can act as a regulatory force of collective life. Our article discusses about the heroes of “settlers” from Rio Grande do Sul which were considered heroes by the memory pioneers regional official for having a different during social conflict known as the Revolt of Squatters in 1957.